Pengaruh Penggunaan Gadget Sejak Dini Terhadap Keterlambatan Bicara Pada Anak Balita - Edi Susilo; Solehudin Solehudin; Risky Kusuma (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Language development is the most important aspect in early childhood. Many children use gadgets as a means of playing. Children who play with gadgets prefer to play with the gadgets they like. The aim of the research is to determine the effect of using gadgets from an early age on speech delays in toddlers. Method; The research is an observational analytic correlation, the research design used is cross sectional. The population in this study were all mothers with toddlers aged 3-5 years in Wonoyoso Village, Pekalongan Regency, totaling 150 and the number of samples was 60. The sampling technique used was purposive sampling. Analysis in this study used the Chi-Square statistical test. Results; the total frequency of using gadgets below 4 times a week is 30 children (96.77%) while those who have a frequency of using gadgets more than 4 times a week are 1 child (3.23%). the use of gadgets with high duration totaled 26 children (76.47%) in the category of children said to be normal in speech and language development, while in the category of children late in language and speech development there were 8 children (13.33%). Conclusion; There is a significant relationship between gadget use and delays in speech and language development in toddlers.